2020
DOI: 10.3390/ma13163648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Filler Wires on Mechanical Property and Conductivity of Aluminum-Copper Joints

Abstract: The 1060 aluminum and T2 copper were joined by the pulsed double electrode gas metal arc welding (DE-GMAW) brazing method by using four types of filler wires, namely pure aluminum (Al) ER1100, aluminum-magnesium (Al–Mg) ER5356, aluminum-silicon (Al–Si) ER4043, and Al–Si ER4047, respectively. The effects of different types of filler wires on intermetallic compounds, microhardness tensile strength, and conductivity of joints were investigated. The results showed that a lot of brittle intermetallic compounds layi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It can be confirmed that, in the Fe-Cu binary system, there are no Fe-Cu intermetallic compounds 6,7) . Based on this, the idea of using pure copper filler metal for dissimilar welding of aluminum and steel was obtained in the study.…”
Section: Introductionmentioning
confidence: 88%
“…It can be confirmed that, in the Fe-Cu binary system, there are no Fe-Cu intermetallic compounds 6,7) . Based on this, the idea of using pure copper filler metal for dissimilar welding of aluminum and steel was obtained in the study.…”
Section: Introductionmentioning
confidence: 88%
“…Li et al 29 considered that it was difficult for Si to form IMCs with Cu or Al due to its non-metallic properties, which can control the growth of IMCs. The joint brazed with Al-12Si filler metal had the highest tensile strength and the joint brazed with Al-5Si filler metal had the highest electrical conductivity 30 . In transient liquid phase bonding with Al-11Si-4Cu-2Mg and Al-4.5Si-1Cu-1Mg interlayer 31 , Mg had no influence on the formation of IMCs and Si decrease the thickness of IMCs by suppressing the growth of CuAl 2 , which lead to a high shear strength and conductivity joint.…”
Section: Introductionmentioning
confidence: 99%